Efektivitas Media Pembelajaran Imla’ Flash Card untuk Meningkatkan Keterampilan Kitabah di MI Ma’arif Sambeng Srandakan - Farid, Miftah (Mahira: Journal of Arabic Studies & Teaching, 2024)
This study aims to examine the effectiveness of the Imla’ Flash Card media in enhancing Arabic writing (Kitabah) skills among third-grade students at MI Ma’arif Sambeng. Additionally, the research evaluates how this instructional media is implemented within the teaching and learning process. Employing a quantitative approach with a quasi-experimental method, the study involved 21 students selected through an exhaustive sampling technique. Data were collected through observation, interviews, tests, and documentation. The hypothesis was tested using the Independent Sample T-Test. The analysis results indicate that the use of Imla’ Flash Card media is effective in improving Arabic writing skills. This is evidenced by the significance value of 0.009, which is less than 0.05, and the increased average post-test score of the experimental class, which reached 81.55, compared to the control class that scored an average of only 64.90. The findings of this research demonstrate that the use of Imla’ Flash Card media is indeed effective in enhancing Arabic writing (Kitabah) skills among students at MI Ma’arif Sambeng.